Obturator vein and its anatomical variations in cadavers: A descriptive study - Sulochana Sakthivel; K V Sarala Devi; Suman Verma (Wolters Kluwer Medknow Publications, 2023)
Background: The obturator vein (OV) is formed in the proximal adductor region and traverses through the obturator foramen to terminate in the internal iliac vein (IIV). It is occasionally replaced by an enlarged pubic vein that terminates into the external iliac vein (EIV) forming a venous corona mortis. These variant OVs are liable to injury during surgical interventions near the pubic bone. The present study aimed to report the prevalence of variant as well as duplicated OVs in Indian cadavers. Methodology: The present descriptive study included 25 adult human cadavers and 11 hemi-pelves. The specimens with variant OVs were identified and followed to their termination into the internal or external iliac system. The external diameter of variant OVs and their distance from the symphysis pubis were recorded. Results: Variant OVs were observed in 34.42%. Most of the variant veins crossed over the pubic ramus. In 21.31%, duplicated OVs were observed, which drained separately into the internal iliac as well as the EIV, or the IIV as a common trunk. The average diameter of the variant OVs on the superior pubic ramus was 4.12 ± 1.2 mm. The average distance between the pubic symphysis and the variant OVs on the superior pubic ramus was 45.28 ± 7.65 mm. Conclusion: The present study appreciates the variant anatomy of the OV and its relation to the superior pubic ramus. Understanding these variations will help avoid the risk of injury and hemorrhage in pelvis surgeries as well as endoscopic procedures.